Complex sSMC Involving X and Y Chromosomes in two Patients with 45,X/46,X,+mar Karyotype (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: molecular cytogenetics; mosaicism sex chromosomes; complex small supernumerary marker chromosome; turner syndrome